The effect of maximal oxygen training at different pulse rates between the groups on some physiological indicators and the achievement of a 200-meter run (Journal of the College of Basic Education, 2022)
The study aimed at the preparation of anaerobic exercises pulse rates between the AGGREGATES and to identify Read more... influence in some physiological indicators and time of completion (200) meters to, researcher pursued an empirical research groups curriculum design throw-away on a sample of Peshmerga Club - sulaimanya selected intentional neglect by (100%) of the community of origin, then into two equal number, the first experimental group apply exercises and reaches the pulse between groups (100.d), the second experimental group apply anaerobic exercises and reaches the pulse between groups (120.d), and the variables of the study of the highest ability and less able anaerobic fatigue index and time of completion (200) meters, with continued application of Filed under anaerobic exercises pulse rates between the two sets of aggregates read more... search for (6) Consecutive training weeks before the competitions at a rate (4) training modules in the training week for the number of overall training units (24) training units in the sports poor (2018), after dealing with the statistical results of the researcher concluded that anaerobic exercises pulse rate in comfort up to help to develop the capacities of ANAEROBIC CP and reduces fatigue and improve achievement indicators long distance (200 meters to anaerobic exercises, the pulse rate in comfort up to help to develop the anaerobic capacity and reduces the signs of fatigue and improve the time of completion of the distance (200 meters to anaerobic exercises, and pulse rate in comfort up to) 100d) best of up to (120 perf... d) in the development and refinement, to suggest that The researcher SERNAM submitted sports training is an ongoing process it is necessary to instability in the codification of Muslim Women Pregnancy training and exit when the anaerobic fixed capacity development to improve the delivery of ran (200) meters, with the need to take into account the balance between work and relaxation training pregnancy when the codification of these exercises.